Indigenous Gold Mining in the Kenkuim Shuar Community: A Decolonial and Postcapitalist Approach to Sustainability - Rickard Lalander; María Beatriz Eguiguren-Riofrío; Ana Karina Vera; Gabriela Espinosa; Maleny Reyes; Magnus Lembke (Revista Iberoamericana de Estudios de Desarrollo, 2021)
This article analyzes the experiences of the small Shuar community of Kenkuim (Congüime) in the Ecuadorian Amazon that since 2016 carries out gold mining through the communitarian company Exploken Minera. The case is unique in South America, not only for being the only example of indigenous mining granted formal state concession, but also for its green profile, without the usage of chemicals or heavy metals. Within a setting of expanding extractivism conditioned by global capitalism and a theoretical framework of a decolonial and postcapitalist approach to sustainability, this ethnographic study deals with the expressions of resistance and adaptation of the Kenkuim community and how socio-cultural, ecological, and economic values are articulated by Shuar actors in relation to the new indigenous mining project. The results indicate that this mining experiment constitutes a meaningful alternative to destructive extractivism in line with decolonial and postcapitalist reasoning.